ANALISIS BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PERUSAHAAN PADA PT XYZ Tbk: ANALISIS BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PERUSAHAAN PADA PT XYZ Tbk - Melvine Rumintang Lumban Batu; Cindy Christine Miranda (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
The performance of a company is a sacrifice made by a person, team, or organization to achieve a particular desire or goal. Measuring company performance is an aspect that is needed or used by certain parties in evaluating company performance or future planning. The balanced scorecard (BSC) can provide a choice of strategic systems that aim to measure work results and improve the organization. The use of a balanced scorecard can also replace business plans and strategies with an organizational benchmark. Currently, there are four aspects of performance measurement in the balanced scorecard, namely the financial aspect, the customer aspect, the internal business aspect, and the learning and growth aspect. From the research results obtained by PT Nippon Indosari Corpindo Tbk for 2021, 2022, and 2023, the company's performance from a financial perspective is in a good position with a liquidity ratio of 265.32%, 209.93%, and 174.11%. Leverage ratio 31.53%, 35.09%, and 39.31%. Profitability ratio 31.53%; 35.09%; and 39.31%. The customer perspective is quite good, as seen from the 2022-2021 period of 17.44% and the 2023-2022 period of 0.83%, with a score of 2. The internal business perspective is in good condition, as seen from the 2022-2021 period of 52.11% and the 2023-2022 period of 22.92%, with a score of 3 and a score of 2. From the learning and growth perspective, from 2021 to 2023, the total number of employees continues to increase, in contrast to the number of employees who leave, which decreases every year. The company continues to improve employee HR training and development, which is carried out continuously every year.